Ukuchichimala kwechweba - Mbungwana, Mthunzikzi (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
iThisisi nepotifoliyo. It is a collection of poems relating to women and society and gender related issues including gender based violence. It also focuses on how Christianity and Xhosa culture has violated women's rights and how they both believe that men and women should have different roles in society.
Keywords: Xhosa poetry